The Future of Logistics Scenarios for 2025 - von der Gracht, Heiko A. (Einkauf, Logistik und Supply Chain Management, 2008)
Scenario planning is considered the most prominent and powerful technique of futures research. There are, however, indications that such planning practices are not widespread in the logistics service industry. Why and to what extend is this so? Based on 51 interviews with logistics CEOs, strategists, and scenario experts, Heiko A. von der Gracht shows that the logistics service industry draws a backward picture of scenario planning practices as compared to other industries. He further elaborates that the potentials of scenario planning in logistics are, nevertheless, exceptionally high. Explorative research has therefore been conducted that comprises a scenario study on the future of the logistics service industry in the year 2025. Based on a two-round modified Delphi survey with 30 top logistics executives a surprising but realistic picture of the future has been drawn. The scenarios are intended to provide a sound planning basis for long-term logistics decisions, to illustrate the value and potentials of the technique, and to exemplify a systematic scenario development.